Trade and development report, 1993 : report by the secretariat of the United Nations Conference on Trade and Development - United Nations Conference on Trade and Development (New York : United Nations, 1993)
The focus of the report is the functioning and interaction of all the different constituent parts of the world economy and of related dimensions of national and international policy. Special attention is given to issues of concern to developing countries. The coverage includes the movements of macroeconomic aggregates in developed and developing countries and in the economies of transition, international trade and trade policies and financial and commodity markets.
'UNCTAD/TDR/13'
rpm 25/08/2016
Loans
Keywords: Growth Dynamics -- The differing parterns; Commerce -- Periodicals; Economic conditions -- Periodicals; International Trade -- Periodicals; International finance -- Periodicals; Developing countries -- Commerce -- Periodicals; Developing countries